2004
DOI: 10.1068/p3346
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Polarities Determine the Direction of Café Wall Tilts

Abstract: We propose an explanatory approach to Café Wall type illusions that is simple yet fairly comprehensive. These illusions are constructed out of basic elementary units in a jigsaw-like manner. Each unit, in general, contains both a solid body and a thin tail: the contrast polarity between the two determines the direction of the contributory illusory tilt produced by that element-according to a heuristic rule illustrated in figure 1. Ensembles of these elements exhibit illusory tilts only when the tails of the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 26 publications
(30 reference statements)
4
37
0
Order By: Relevance
“…A variety of luminancebased illusions akin to the Cafe¨Wall illusion have recently been presented by Kitaoka (1998) and by Kitaoka et al (2004). The experimental data presented here agree with their observations on the direction of the distortions.…”
Section: Discussionsupporting
confidence: 91%
“…A variety of luminancebased illusions akin to the Cafe¨Wall illusion have recently been presented by Kitaoka (1998) and by Kitaoka et al (2004). The experimental data presented here agree with their observations on the direction of the distortions.…”
Section: Discussionsupporting
confidence: 91%
“…Ninio and O'Regan (1996) suggested this effect as one among several possible sources of the Zöllner illusion. Pairs of forces of opposite directions, exerting a torque were also invoked by Kitaoka, Pinna, and Brelstaff (2004) to explain the tilts observed in the illusions of the café-wall family, which could be related to the Zöllner illusions. However, we prefer to leave this class of illusions out of the scope of the present analysis.…”
Section: Expansion Illusionsmentioning
confidence: 99%
“…They showed that twisted cords are implicitly in the café wall pattern. Recently Kitaoka et al gave a phenomenological explanation in terms of contrast polarities ( [14]). There are also other studies about the café wall illusion.…”
Section: Simultaneous Contrast and Todorovic's Illusionmentioning
confidence: 99%
“…There are also other studies about the café wall illusion. For a brief history of this illusion, see Kitaoka et al [14].…”
Section: Simultaneous Contrast and Todorovic's Illusionmentioning
confidence: 99%